Hak Anak Stateless Person Korban Tindak Pidana Kejahatan Seksual Menurut Hukum Positif di Indonesia - Rinaldi, Rinaldi; Ikhsan, Edy; Ekaputra, Mohammad (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Sexual crimes against children remain a critical and persistent issue in Indonesia. Child victims are especially vulnerable, and their rights are often marginalized within legal processes. Although Indonesia has ratified the Convention on the Rights of the Child and enacted relevant laws such as the Child Protection Law, significant gaps remain in their implementation. This study focuses on stateless children who are victims of sexual crimes—an especially marginalized group that suffers not only from the crime itself but also from legal invisibility. The central question addressed is how Indonesian positive law recognizes and protects the rights of these stateless child victims. Employing a normative juridical method, this research examines the relevant legal instruments and judicial practices in Indonesia. The findings reveal three key issues: first, existing legal protections for child victims are inconsistently applied; second, Indonesia’s non-ratification of the 1951 Refugee Convention means that stateless persons lack formal legal status, limiting their access to justice; third, the absence of legal identity and citizenship further exacerbates the vulnerability of stateless children. The study concludes that while legal frameworks are in place, meaningful protection for stateless child victims demands both legal innovation and a stronger commitment to the principle of the best interests of the child.